2018
DOI: 10.1002/ange.201706535
|View full text |Cite
|
Sign up to set email alerts
|

Modulating Cell‐Surface Receptor Signaling and Ion Channel Functions by In Situ Glycan Editing

Abstract: Supportinginformation and the ORCID identification number(s) for the author(s) of this article can be found under: https://doi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Recently, due to the creation of the expression vector library encoding all known human glycosyltransferases by Moremen et al, any human glycosyltransferase of interest can now be produced as secreted catalytic domain GFP-fusion proteins in mammalian and insect cell hosts 47 . Studies by Boons, Steet and coworkers and by our own lab have demonstrated that several enzymes produced by this system are highly efficient for cell-surface chemoenzymatic glycan modification 2,9,48 . However, this approach is associated with relatively high cost.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Recently, due to the creation of the expression vector library encoding all known human glycosyltransferases by Moremen et al, any human glycosyltransferase of interest can now be produced as secreted catalytic domain GFP-fusion proteins in mammalian and insect cell hosts 47 . Studies by Boons, Steet and coworkers and by our own lab have demonstrated that several enzymes produced by this system are highly efficient for cell-surface chemoenzymatic glycan modification 2,9,48 . However, this approach is associated with relatively high cost.…”
Section: Discussionmentioning
confidence: 93%
“…Complementary to metabolic oligosaccharide engineering (MOE) 1 , chemoenzymatic glycan labeling and modification have emerged as valuable tools to modify glycan structures within a cellular environment 2–4 . Unlike MOE, which relies on a cell or an organisms’s own glycan biosynthetic mechinary to incorporate unnatural monosaccharides with linkage promiscuity, chemoenzymatic glycan modification utilizes a recombinant glycosyltransferase to transfer natural or unnatural monosaccharides with novel functions from activated nucleotide sugars to glycoconjugates on the cell surface with linkage specificity.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Note that the most important membrane transporters in cancer cells are the ATP-dependent Na + , K + , 2Cl − co-transporter NKCC1, the Na/K ATPase, cation channels, and the Na + /H + exchanger NHE1 [ 52 ]. Therefore, it seems reasonable to suggest that changes in the size and chemical composition of the membrane glycans at the melanoma cell surface are responsible for developmental and cell-specific variability in the biophysical and functional properties of many ion channels [ 53 ]. The present study evidenced that the structure of α 1-acid glycoprotein composing of ca.…”
Section: Resultsmentioning
confidence: 99%